2013
DOI: 10.1038/onc.2013.347
|View full text |Cite
|
Sign up to set email alerts
|

Insulin activates the insulin receptor to downregulate the PTEN tumour suppressor

Abstract: Insulin and insulin-like growth factor-1 signaling have fundamental roles in energy metabolism, growth and development. Recent research suggests hyperactive insulin receptor (IR) and hyperinsulinemia are cancer risk factors. However, the mechanisms that account for the link between the hyperactive insulin signaling and cancer risk are not well understood. Here we show that an insulin-like signaling inhibits the DAF-18/(phosphatase and tensin homolog) PTEN tumour suppressor in Caenorhabditis elegans and that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 47 publications
(60 reference statements)
1
18
0
Order By: Relevance
“…11a ). Protein levels of the PKB negative regulator PTEN are reduced by IR overexpression 42 , and in accordance we detected low PTEN levels in BACE1 −/− livers (Fig. 6e and Supplementary Fig.…”
Section: Resultssupporting
confidence: 86%
“…11a ). Protein levels of the PKB negative regulator PTEN are reduced by IR overexpression 42 , and in accordance we detected low PTEN levels in BACE1 −/− livers (Fig. 6e and Supplementary Fig.…”
Section: Resultssupporting
confidence: 86%
“…Both Ser/Thr and tyrosine phosphorylation are known to regulate PTEN phosphorylation (44). Two studies reported tyrosine phosphorylation of PTEN by key RTK signaling molecules (namely Eph and IR) at various tyrosine residues, which results in destabilization and further downregulation of PTEN (45)(46)(47). However, Yim et al (48) showed that Rak tyrosine signaling phosphorylates Y336 and stabilizes PTEN.…”
Section: Negative Association Of Grb10 With Ptenmentioning
confidence: 99%
“…Moreover, insulin signaling was found to inhibit PTEN expression (Liu et al 2014), and insulin resistance has been linked to increased FASN expression (Menendez et al 2009), indicating that aberrant insulin signaling may underlie altered PTEN and FASN expression levels and activity in CRC. To evaluate whether Lun, Gen, and/or MET attenuate CSC frequency by opposing insulin action, we exposed HCT116 cells to an elevated level of insulin (2 lM, modeling hyperinsulinemia) and determined effects of added factors on colonosphere formation and on the CD133 ?…”
Section: Soy Bioactive Components Alter Hct116 Cell Viability Apoptomentioning
confidence: 99%